Identifying the Switching Determinants of Mobile Enterprise Customers : The Perspective of Pull - Push - Mooring Model and Mobile Number Portability - Babu, C. N. S. Ramnath; Sundar, S. (Indian Journal of Marketing, 2019)
This study aimed at finding out the key determinants of switching behaviour among the enterprise customers of mobile network operators based on the push - pull - mooring theory and to ascertain the influence of mobile number portability on switching behaviour. An extensive review of literature coupled with focus group discussion and 11 one-to-one in-depth interviews provided the impetus to the design and development of the survey instrument, which was then administered through e-mail to the enterprise customers in rest of Tamil Nadu telecom circle. This descriptive research study adopted multi-stage, non-probability sampling method and convenience sampling technique to administer the field and e-mail survey to collect the primary data. This study identified the push factors (network services, billing system, service encounters, technology, and convenience) and pull factors (reputation, brand image, word-of-mouth recommendation, and pricing) that caused switching as well as the mooring factor (switching cost) that influenced the customers’ decision to stay with or switch from the current in-use service provider. These factors will help mobile network operators (MNOs) to identify unsatisfied customers and to optimally allocate marketing resources to retain them satisfied and loyal to the brand, and also to acquire new customers.